Analisis Strategi Kreatif Pembelajaran Teori Kognitif dalam Meningkatkan Semangat Belajar Matematika Siswa Kelas 5 Sekolah Dasar - Ratnasari, Mila; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to overcome this problem by analyzing the positive impact of creative strategies based on cognitive theory on the enthusiasm for learning mathematics in grade 5 elementary school students. Through a quasi-experimental design with an experimental group and a control group, this research uses quantitative methods to collect and analyze data. The research results showed a significant increase in understanding of mathematical concepts and enthusiasm for learning in the experimental group who applied creative strategies. More interactive class dynamics and more active student participation also support the successful implementation of this strategy.